Procedure for application of remote educational technologies by university teachers - Sokolovska, I.; Plakhotnik, O.; Nechyporenko, V.; Pozdniakova, O.; Hordiienko, N.; Nechyporenko, K.; Siliavina, Yu.; Mavrin, V.; Semeniv, I.; Kotuza, A.; Yunger, V.; Zazirny, I.; et al. (My University, 2022)
Inflammatory diseases cause health disorders which result in a reduction of the population. That is why this medical problem is considered to be a very important one. The human immune system is responsible for protecting the body from infections of various origins, while inducing chronic inflammation (characterized by a long, often invisible course) which can result in proneness to recurrence, complications and resistance to therapy. The authors of the article analyzed and proved that there are immune status shifts in patients with chronic nonspecific inflammatory processes depending on the pathogen, phase and level of damage.
Keywords: immunity; chronic inflammatory process; infectious agents; the stagnation of the organism's reactivity; integral hematological indicators